2023
DOI: 10.1186/s13054-023-04469-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of airway pressure release ventilation on lung physiology assessed by electrical impedance tomography in patients with early moderate-to-severe ARDS

Abstract: Objective The aim of this study was to investigate the physiological impact of airway pressure release ventilation (APRV) on patients with early moderate-to-severe acute respiratory distress syndrome (ARDS) by electrical impedance tomography (EIT). Methods In this single-center prospective physiological study, adult patients with early moderate-to-severe ARDS mechanically ventilated with APRV were assessed by EIT shortly after APRV (T0), and 6 h (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Our findings did not show that the GI index decreased over time. This is in contrast to previous pediatric and adult studies, which showed a reduction of inhomogeneity over time [ 17 , 32 ]. However, it should be acknowledged that our time intervals between data collection points were relatively short in comparison to those utilized in the aforementioned studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings did not show that the GI index decreased over time. This is in contrast to previous pediatric and adult studies, which showed a reduction of inhomogeneity over time [ 17 , 32 ]. However, it should be acknowledged that our time intervals between data collection points were relatively short in comparison to those utilized in the aforementioned studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A systematic review focusing on observational studies of trauma-related ARDS suggested that early implementation of APRV may reduce mortality in this specific population [ 20 ]. Furthermore, for patients with moderate to severe ARDS, early application of APRV can improve ventilation-perfusion ratio and lung heterogeneity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials (RCTs) has proven the significant advantages of APRV utilization, as it contributes to lower mortality, shortens the length of stay on a ventilator, and improves lung compliance and oxygenation status [ 24 ]. Notwithstanding, recent evidence has shown that the indication and effectiveness of APRV remain ambiguous due to a lack of robust evidence supporting the purported benefits of APRV [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%